1977
DOI: 10.1037/h0077304
|View full text |Cite
|
Sign up to set email alerts
|

Medial preoptic area and onset of maternal behavior in the rat.

Abstract: The present series of experiments examined whether the medial preoptic area (MPOA) is involved in the onset of maternal behavior in the rat. Previously, the MPOA had been shown to be important in the maintenance of maternal behavior in the lactating rat. The first experiment investigated whether estradiol benzoate (EB) acts on the MPOA to facilitate the onset of maternal behavior in the 16-day pregnant, hysterectomized, and ovariectomized female rat. Such rats when given EB implants in the MPOA had significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
200
0
12

Year Published

1996
1996
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 380 publications
(226 citation statements)
references
References 45 publications
9
200
0
12
Order By: Relevance
“…The MPOA is importantly involved in the onset and maintenance of maternal care (15,22,(25)(26)(27), and local AVP-Rs have been described (31). Here, we found increased AVP-R binding within the MPOA in lactating compared with virgin rats (P Ͻ 0.05; Fig.…”
Section: Down-regulation Of Avp-r In the Mpoa Decreased Maternal Caresupporting
confidence: 58%
See 2 more Smart Citations
“…The MPOA is importantly involved in the onset and maintenance of maternal care (15,22,(25)(26)(27), and local AVP-Rs have been described (31). Here, we found increased AVP-R binding within the MPOA in lactating compared with virgin rats (P Ͻ 0.05; Fig.…”
Section: Down-regulation Of Avp-r In the Mpoa Decreased Maternal Caresupporting
confidence: 58%
“…The MPOA is important for the onset and maintenance of maternal care, including retrieval of pups (15,22,(25)(26)(27). Within the MPOA, local AVP-Rs were found to be up-regulated during lactation (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence for the importance of receptor differences at the level of the MPOA is certainly compelling. Infusions of either estrogen (14,33) or oxytocin (22) directly into the MPOA facilitate the expression of maternal care. Moreover, lesions of the MPOA decrease pup licking͞grooming (34).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, s.c. injections of virgin rats with higher doses of EB stimulated maternal care towards foster young (Siegel and Rosenblatt, 1975b). Subsequent central studies designed to identify a possible neural site of estradiol stimulation of maternal behavior demonstrated that direct bilateral implants of dilute estradiol into the MPOA of either pregnancy-terminated primigravid rats (Numan et al, 1977) or ovariectomized, virgin rats (Fahrbach and Pfaff, 1986) produced shorter response latencies towards foster test young. The actions of estrogen in promoting maternal care in mice appear to be mediated via the estrogen alpha receptor (Riberio et al, 2012).…”
Section: Factors Affecting Offspring-directed Behaviorsmentioning
confidence: 99%